A comunicação nas práticas de jovens professores de Matemática - João Pedro da Ponte; António Guerreiro; Helena Cunha; José Duarte; Helena Martinho; Cristina Martins; Luís Menezes; Hugo Menino; Hélia Pinto; Leonor Santos; José Manuel Varandas; Luciano Veia; et al. (Universidade do Minho, 2007)
This article aims to know the way how new teachers, at several teaching levels, recently graduated by pre-service teacher education institutions, view and conduct communication in their classrooms, to which aspects they tend to pay attention and which difficulties they feel. The text is based on a collective work carried out by teacher educators of teacher education institutions in Portugal that are concerned in improving the quality of the pre-service teacher education, especially in what refers to mathematics education. The methodology is qualitative and interpretative and involved the realization of 12 case studies. The results show that communication is seen by the new teachers as a support of a general environment that must favour learning. However, only relatively few teachers point out communication as an important curriculum objective in the discipline of mathematics and indicate consistent strategies to promote it, both in oral and written forms. There are still less teachers who view communication as a basic process for the development of mathematical meanings by students. These results suggest that teacher education institutions may have interest in reflecting about their teaching practices in this regard.